Investment Cost Analysis of Renewable Energy Plant Development in Bali Province - I K. S. T. Lilayoga; W. G. Ariastina; D. A. S. Santiari; I. A. D. Giriantari; I N. Setiawan; I W. Sukerayasa; I N. S. Kumara (Journal of Electrical, Electronics and Informatics, 2025)
Bali Province is one of the areas that has abundant renewable energy potential. Through increasing the role of renewable energy in the national energy mix which is a government program, which aims to reduce the use of non-renewable energy and open community participation in utilizing renewable energy in Bali Province. To overcome these problems, an analysis of the investment costs of developing renewable energy plants in Bali Province in 3 scenario modeling was carried out. In this scenario modeling is carried out to determine the investment cost of developing renewable energy plants in Bali Province in the 2024 - 2045 time span. The results of this study show that renewable energy investment costs in the optimistic scenario require investment costs of 264,12 Million USD in 2024 increasing to 2.078,35 Million USD in 2045 with total investment costs during the modeling period of 46.477,10 Million USD. The moderate scenario requires investment costs of 264,12 Million USD in 2024 increasing to 1.186,30 Million USD in 2045 with total investment costs during the modeling period of 27.362,52 Million USD. The pessimistic scenario requires investment costs of 264,12 Million USD in 2024 increasing to 986,80 Million USD in 2045 with total investment costs for the modeling period of 20.817,04 Million USD.